Sharing Sequential Values in a Network - JUAREZ, Ruben (Institutional Knowledge at Singapore Management University, 2016)
Consider a sequential process where agents have individual values at every possible step. A planner is in charge of selecting steps and distributing the accumulated aggregate values among agents. We model this process by a directed network where each edge is associated with a vector of individual values. This model applies to several new and existing problems, e.g., developing a connected public facility and distributing total values received by surrounding districts; selecting a long-term production plan and sharing final profits among partners of a firm; choosing a machine schedule to serve different tasks and distributing total outputs among task owners. Herein, we provide the first axiomatic study on path selection and value sharing in networks. We consider four sets of axioms from different perspectives, including those related to (1) the sequential consistency of assignments with respect to network decompositions; (2) the monotonicity of assignments with respect to network expansion; (3) the independence of assignments with respect to certain network transformations; and (4) implementation in the case where the planner has no information about the underlying network and individual values. Surprisingly, these four disparate sets of axioms characterize similar classes of solutions — selecting efficient path(s) and assigning to each agent a share of total values which is independent of their individual values. Furthermore, we characterize more general solutions that depend on individual values.